Rara avis in Ultima Thule: Praefatio / Preface - Aspaas, Petrus Pippinus; Albert, Sigrides; Nilsen, Fridericus (Nordlit, 2014)
This book is a Festschrift dedicated to Synnøve des Bouvrie, professor of classical studies at UiT The Arctic University of Norway, who celebrates her seventieth birthday on 16th November 2014. Apart from the introduction, the Festschrift is divided into four parts, namely a Pars Mythologica, Philosophico-Litteraria, Thulensis, and Latinitatis Vivae. Twelve articles have been written in English, seven in Latin, four in Norwegian and a single article in each of the languages French, Sami and Swedish. A biographical interview is also included, along with several illustrations made by Synnøve herself. The book has been edited by Per Pippin Aspaas (Tromsø), Sigrid Albert (Saarbrücken) and Fredrik Nilsen (Tromsø).